Points of departure: rethinking student source use and writing studies research methods - Serviss, Tricia, editor; Jamieson, Sandra, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Encourages a return to empirical research about writing, presents transparent, reproducible studies of student sources. How to develop methods for coding and characterizing student texts, their choice of source material, and the resources used to teach information literacy, and advances understanding of how students actually write.--Provided by publisher.
Introduction. The rise of RAD research methods in writing studies: transcontextual ways forward / Tricia Serviss -- Interchapter: what do we mean by transcontextual RAD research? -- The evolution of the citation project: developing a pilot study from local to translocal / Sandra Jamieson -- Reports from the LILAC project: designing a translocal study / Katt Blackwell-Starnes and Janice R. Walker -- Points of departure: replication and the need to build on and expand local and pilot studies -- Interchapter: what does design-based research offer as a tool for RAD research in writing studies? -- The things they carry: using design-based research in writing teacher education / Tricia Serviss -- Storied research: using focus groups as a responsive method / Crystal Benedicks -- Terms and perceptions: using surveys to discover student beliefs about research / Kristi Murray Costello -- Points of departure: developing design-based local and translocal studies -- Interchapter: what does threshold concept research offer writing studies RAD research? -- Research and rhetorical purpose: using genre analysis to understand use in technical and professional writing / Lee-Ann Kastman Breuch and Brian N. Larson -- Asking the right questions: using interviews to explore information seeking behavior / Whitney Olsen and Anne Diekema -- Just read the assignment: using course documents to analyze research pedagogy / Elizabeth Kleinfeld -- Points of departure: using existing research to think beyond the local -- Afterword. Teaching hybridity in graduate research courses / Rebecca Moore Howard.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Research; Academic writing -- Study and teaching -- Research; Report writing -- Study and teaching -- Research; Research -- Methodology